Eudiplozoon nipponicum (Monogenea, Diplozoidae) and its adaptation to haematophagy as revealed by transcriptome and secretome profiling - Vorel, Jiří; Cwiklinski, Krystyna; Roudnický, Pavel; Ilgová, Jana; Jedličková, Lucie; Dalton, John P; Mikeš, Libor; Gelnar, Milan; Kašný, Martin (BMC genomics, 2021)
BACKGROUND: Ectoparasites from the family Diplozoidae (Platyhelminthes, Monogenea) belong to obligate haematophagous helminths of cyprinid fish. Current knowledge of these worms is for the most part limited to their morphological, phylogenetic, and population features. Information concerning the biochemical and molecular nature of physiological processes involved in host-parasite interaction, such as evasion of the immune system and its regulation, digestion of macromolecules, suppression of blood coagulation and inflammation, and effect on host tissue and physiology, is lacking. In this study, we report for the first time a comprehensive transcriptomic/secretome description of expressed genes and proteins secreted by the adult stage of Eudiplozoon nipponicum (Goto, 1891) Khotenovsky, 1985, an obligate sanguivorous monogenean which parasitises the gills of the common carp (Cyprinus carpio). RESULTS: RNA-seq raw reads (324,941 Roche 454 and 149,697,864 Illumina) were generated, de novo assembled, and filtered into 37,062 protein-coding transcripts. For 19,644 (53.0%) of them, we determined their sequential homologues. In silico functional analysis of E. nipponicum RNA-seq data revealed numerous transcripts, pathways, and GO terms responsible for immunomodulation (inhibitors of proteolytic enzymes, CD59-like proteins, fatty acid binding proteins), feeding (proteolytic enzymes cathepsins B, D, L1, and L3), and development (fructose 1,6-bisphosphatase, ferritin, and annexin). LC-MS/MS spectrometry analysis identified 721 proteins secreted by E. nipponicum with predominantly immunomodulatory and anti-inflammatory functions (peptidyl-prolyl cis-trans isomerase, homolog to SmKK7, tetraspanin) and ability to digest host macromolecules (cathepsins B, D, L1). CONCLUSIONS: In this study, we integrated two high-throughput sequencing techniques, mass spectrometry analysis, and comprehensive bioinformatics approach in order to arrive at the first comprehensive description of monogenean transcriptome and secretome. Exploration of E. nipponicum transcriptome-related nucleotide sequences and translated and secreted proteins offer a better understanding of molecular biology and biochemistry of these, often neglected, organisms. It enabled us to report the essential physiological pathways and protein molecules involved in their interactions with the fish hosts.
Keywords: Secretome; Gene Expression Profiling; NGS; transkriptom; Eudiplozoon nipponicum; kapři; anotace sekvence; Transcriptome; Molecular Sequence Annotation; Carps; zvířata; Annotation; Monogenea; Tandem Mass Spectrometry; fylogeneze; Mass spectrometry; chromatografie kapalinová; Trematoda; stanovení celkové genové exprese; tandemová hmotnostní spektrometrie; Assembly; Chromatography, Liquid; Phylogeny; Animals